Calderón’s ambiguity with respect to the moriscos in «El Tuzaní de la Alpujarra» - Devos, Brent W. (Anuario Calderoniano, 2014)
Most of the critical attention given to El Tuzaní de la Alpujarra by Pedro Calderón de la Barca over the past three decades has been focused on the question of playwright’s ideological position with respect to the Moriscos. This study continues this line of inquiry, but challenges the nearly unanimous conclusion that Calderón manifests in El Tuzaní a tolerant, even sympathetic attitude regarding the minority. By means of a detailed study of the characterization of Morisco and old Christian characters in several key scenes, and by placing the play in the context in which it appeared, this study argues that El Tuzaní manifests both the anti-Morisco prejudices and the literary Morisco stereotypes of its time, and that the playwright’s ideological position vis-à-vis the minority is ambiguous. «La ambigüedad calderoniana en relación a los moriscos en El Tuzaní de la Alpujarra» La mayoría de la atención crítica que ha recibido El Tuzaní de la Alpujarra de Pedro Calderón de la Barca durante las últimas tres décadas ha sido enfocada en la cuestión de la postura ideológica de Calderón con respecto a los moriscos. Este estudio sigue en esta línea, pero desafía la conclusión casi unánime en la crítica reciente de que Calderón manifiesta en El Tuzaní una postura tolerante e incluso simpatizante en cuanto a la minoría. A través de un estudio detallado de la caracterización de los personajes moriscos y viejo-cristianos en varias escenas claves, y teniendo en cuenta el contexto en el que apareció la comedia, se demuestra que El Tuzaní manifiesta los estereotipos literarios y los prejuicios anti-moriscos de su época, y que la postura ideológica del dramaturgo con respecto a la minoría es ambigua. PALABRAS CLAVE / KEYWORDS: Calderón, El Tuzaní de la Alpujarra, moriscos, personajes, temas / Calderón, El Tuzaní de la Alpujarra, moriscos, characters, themes.